PEMBUATAN GAME RHYTHM “RHYTHM HOLIC!” PADA PLATFORM ANDROID - Jastin Ng; Jeanny Pragantha; Darius Andana Haris (Fakultas Teknologi Informasi Universitas Tarumanagara, 2020)
“Rhythm Holic” is a 2D Rhythm game for Android. This game uses Unity2D as it game engine and targeted to Android mobile phone. The game design are designed using Unity as it platform and Microsoft Visual Studio for the game script. Player can select all of the 10 song in-game that include EDM, Pop, Art and indie song. In the game the song Beats Per Minute(BPM) varies from as low as 85BPM to as high as 179BPM. All of the song inside the game were unlocked so player can choose which song the player want to play. Player can save the high score by offline service and can be reset via option menu to reset it. Testing was done by the blackbox testing, alpha testing by lecturer, and beta testing by surveying 32 respondens. Test results show that responden got interest while playing because the game was fun, entertaining and the background is interesting. Although the game are fun and entertaining for some player it got some cons that was the tap area was not strategic enough and the appearing not was too little and scroll speed was not fast enough.